Processes Driving Iron and Manganese Dispersal From the TAG Hydrothermal Plume (Mid-Atlantic Ridge): Results From a GEOTRACES Process Study - González-Santana, David; Planquette, Hélène; Cheize, Marie; Whitby, Hannah; Gourain, Arthur; Holmes, Thomas; Guyader, Vivien; Cathalot, Cécile; Pelleter, Ewan; Fouquet, Yves; Sarthou, Géraldine (Frontiers in Marine Science, 2020)
While hydrothermal vents are a recognized source of trace elements to the ocean inventory, the contribution of slow-spreading ridges remains poorly resolved. To address this, high-resolution dissolved (<0.45µm) iron (dFe) and manganese (dMn) samples were collected during the GEOTRACES HERMINE GApr07 process study at the Mid Atlantic Ridge. Samples were collected at nine stations, from the TAG vent site to 75 km south-southwest following the neutrally buoyant plume. Concentrations of dMn and dFe ranged from 71 ± 6 and 51 ± 2 nmol kg-1 right above the vent site to 0.43 ± 0.01 and 1.56 ± 0.02 nmol kg-1 at the most distal station, respectively. Using a 5-box model coupled with our data, we show that as the plume travelled away from the vent, aggregation processes controlled dFe concentrations in the first 2 km, with an aggregation rate averaging between 8.0 ± 0.6 and 0.11 ± 0.04 nmol L-1 d-1, respectively in the first and second kilometer. Aggregation likely of small colloidal particles, led to partitioning of the size fractionated Fe pool, as 6% of the dFe was moved into the particulate size fraction. Further away, disaggregation processes became more prevalent, with rates ranging from 0.27 ± 0.02 to 0.008 ± 0.001 nmol L-1 d-1, enriching the dFe pool by 10 %. The computed decrease of hydrothermal Fe within the neutrally buoyant plume was likely caused by flocculation of small Fe oxyhydroxide particles. This process resulted in Fe aggregate formation with radii estimated to range from 18 ± 1 µm in the first km from TAG to 2.5 ± 0.4 and 6 ± 2 µm between 1 and 30 km from the vent site.